Orthotopic Kidney Transplant as a Fifth Intra-Abdominal Organ after Two Previous Kidney and Two Previous Pancreas Transplants. (30th June 2022) - Al-Adwan, Yazan; Singh, Navdeep; Rajab, Amer; Alebrahim, Musab; Subramanian, Jayanthan; Washburn, W. Kenneth; Siddiqui, Farjad; Limkenmann, Ashley; Chotai, Pranit N.; Schenk, Austin
Abstract : Background . Patients with more than two prior kidney transplant procedures pose unique surgical challenges. Once both the right and left retroperitoneal spaces have been dissected, intra-abdominal implantation is usually necessary. If the external iliac arteries have been used previously, it is sometimes necessary to use the aorta and vena cava for implantation. Gaining safe exposure in these cases can be complicated by history of prior laparotomy, adhesive disease, and other surgical histories. Case Presentation . A 58-year-old female with type 1 diabetes and end-stage renal disease presented for surgical evaluation for kidney transplant. Surgical history was notable for prior simultaneous kidney-pancreas transplant followed by both a living donor kidney transplant and a pancreas after kidney transplant. She had undergone both an allograft nephrectomy and an allograft pancreatectomy and currently had a nonfunctioning kidney in the left retroperitoneal position and a nonfunctioning pancreatic allograft on the right common iliac artery. The entire distal aortoiliac system was surgically inaccessible. She was listed for transplantation, and a cadaveric graft was allocated. Intraoperatively, severe lower abdominal and pelvic adhesions prevented any use of the iliac system. A left native nephrectomy was performed, and the allograft was implanted in the left orthotopic position. The native left renal vein was used for outflow, the donor renal artery was joined end-to-side to the infrarenal aorta, and a uretero-ureterostomy was created. The operation was uneventful. The allograft functioned without delay, and almost one year later, the GFR is approximately 50 mg/dL. Conclusion . The left orthotopic position can be a good choice for kidney transplant candidates with histories of prior complex lower abdominal surgery.